SERIOUS VIOLATIONS OF HUMAN RIGHTS AGAINST PEASANTS DURING THE MILITARY DICTATORSHIP (1964-1985) - Covre Marchiori, Pedro (Revista Gênero e Interdisciplinaridade, 2022)
The objective of this project is to analyze the reports of the National Truth Commission (CNV), the book-report “Right to Memory and Truth” of the Special Commission on Political Deaths and Disappearances, and the “Portrait of Political Repression in Campo Brasil 1962- 1985 , Tortured, dead and dead camps”, the result of commissions that 2 disappeared in Brazil for 2 years 017 to reflect on human rights graves that were recorded during the military dictatorship (1964-1985). The expression “human violation” elaborated in this text by the treaties is the same embodied that was characterized as human rights of violation of humanity”, so that it specifically deals with violations of the laws of the Brazilian State / or at its command, against the civilian population, intensely and continuously, with permanent use of force.